Chemical constituents from fruits of Hydnocarpus hainanensis Merr. (Flacourtiaceae) in Vietnam - Tra, Nguyen Thanh; Ngan, Truong Bich; Mai Huong, Doan Thi; Litaudon, Marc; Hung, Nguyen Van; Thao, Do Thi; Minh, Chau Van; Cuong, Pham Van (Vietnam Journal of Chemistry, 2015)
Five compounds were isolated from the fruits of Hydnocarpus hainanensis Merr. Sleum. (Flacourtiaceae). Their structures were determined by spectroscopic analysis including MS and NMR. The isolates were identified as taraktophyllin (1), hydnocarpic acid (2), 3,4-dihydroxybenzyl alcohol (3), 3,4-dihydroxybenzoic acid (4) and 3-hydroxy-4-methoxybenzoic acid (5).